2015
DOI: 10.1073/pnas.1514282112
|View full text |Cite
|
Sign up to set email alerts
|

The K + channel K IR 2.1 functions in tandem with proton influx to mediate sour taste transduction

Abstract: Sour taste is detected by a subset of taste cells on the tongue and palate epithelium that respond to acids with trains of action potentials. Entry of protons through a Zn2+-sensitive proton conductance that is specific to sour taste cells has been shown to be the initial event in sour taste transduction. Whether this conductance acts in concert with other channels sensitive to changes in intracellular pH, however, is not known. Here, we show that intracellular acidification generates excitatory responses in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 59 publications
0
75
0
1
Order By: Relevance
“…In general, bitter, sweet and umami stimuli are detected by type II cells 13 , sour stimuli are detected by type III cells 46 , and salty (NaCl) stimuli are detected by as-yet-undefined taste bud cells 7 . Below, we describe the mechanisms by which gustatory stimuli are transduced by taste buds.…”
Section: Chemosensory Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, bitter, sweet and umami stimuli are detected by type II cells 13 , sour stimuli are detected by type III cells 46 , and salty (NaCl) stimuli are detected by as-yet-undefined taste bud cells 7 . Below, we describe the mechanisms by which gustatory stimuli are transduced by taste buds.…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…The influx of protons through the channel generates a small depolarizing current, and furthermore, the accumulation of protons inside the cell contributes to the inhibition of KIR2.1 channels. The net result in both cases is depolarization of the type III sour-sensing cells such that they reach the threshold for action potential initiation 6 .…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…This indicates that lateral inhibition is significant in taste perception. We suggest that this is indicative that taste is enhanced through lateral inhibition, which has been demonstrated in mice during sour taste transduction through intracellular acidification [62]. Although there is not much research regarding lateral inhibition in gustatory response, it has been shown that axonal branches are capable of inhibiting the same or lateral taste units, because neurons can activate inhibitory neighboring interneurons, producing action potentials [76].…”
Section: Lateral Inhibition In Gustationmentioning
confidence: 73%
“…In the cortices that correspond to vision, audition, and mechanoreception, a stimulus can synaptically excite or inhibit any or all stimuli through "co-tuning"; however, in rats, the pyramidal cells in the neocortex prevent "co-tuning" through balance and regulation of "input and spike timing in the piriform cortex" [61]. In experiments using mice, newer findings indicate that amplification in smell occurs as calcium enters cyclic-nucleotide gated ion channels and reacts with chloride channels resulting in membrane depolarization, giving the mice the ability to smell when ion concentrations are limited [62]. In humans, the ability to adapt to an odorant is possible through physiological processes that include: 1) protein kinase phosphorylation of a receptor that can inactivate or desensitize an odorant receptor following odorant receptor and ligand interaction, and 2) odorant sensitivity adjusted by the cyclic nucleotide gated ion channels to cAMP-which is similar to how the visual system adapts to light intensity matched by environmental light intensity [63].…”
Section: Lateral Inhibition In Olfactionmentioning
confidence: 99%
“…The sour taste machinery has begun to emerge in recent years, but the intracellular response underlying sour taste detection is not known. In PNAS, Ye et al (3) report a potassium (K + ) channel as a key component of sour taste transduction, which fills a significant gap in the field.…”
mentioning
confidence: 99%